“The broken schippus he ther fonde”: Shipwrecks and the Human Costs of Investment Capital in Middle English Romance - Richmond, Andrew M. (Neophilologus, 2015)
Featuring prominently in the romance imagination as terrifying obstacles in the hero’s path, shipwrecks are nevertheless often presented from the salvager’s perspective. Romances abound with knights, clerks, and merchants who obsessively observe nearby beaches and cautiously (yet excitedly) examine the contents of wrecked vessels. Washed ashore, such fruits of maritime disaster delineate medieval English conceptions of seashores as dangerous yet profitable spaces, wherein seaside harvests of (un)natural resources help to stimulate local economic networks. Designations of these shipwrecks as “magical” or “fortuitous” cannot, however, completely elide the source of such wealth in others’ suffering—an unavoidable implication that interrogates contemporary means of attaining investment capital. As such, this paper examines how the littoral space of the seashore is cast as a source of perilous and problematic material bounty in many Middle English romances.
Keywords: Emaré; Geoffrey Chaucer; John Gower; Middle English romance; Shipwrecks; Sir Amadace; dept.eng

Affect, Semiotics, Volition: Heteroregulation and Affectivating. - Larocco, Steve (I Activate You To Affect Me, 2018)
The second volume of Annals of Cultural Psychology is dedicated to the affective nature of human social relationships with the environment. The chapters here included explore the historical, theoretical and practical dimensions of the concept of affectivating originally introduced by one of us (Valsiner, 1999), as a potential tool of inquiry into the affective-sensitive dimension of psychological life within a cultural-psychological framework. The concept of affectivating involves two psychological dimensions often undervalued or even obliterated from contemporary cultural psychology, namely the affective involvement and the agentivity of people in their social encounters. Through several examples --‘feeling-at-home’, silence spaces and rituals, memorials, music and poetry, among others-- we show individual’s concrete actions in mundane everyday life aim to give an affective personal sense to the world around. This focuses on the primary affective nature of human meaning construction that guides the person in one’s continuing feeling-into-the-world. At a theoretical level the notion of affectivation challenges contemporary Cultural Psychology to rescue subjectivity, not only symbolism. Affectivation propounds a return to the long, but partially forgotten, organismic tradition, represented in the history by thinkers like Wilhelm Dilthey, Jakob von Uexküll and Kurt Goldstein. Cultural psychology has to bring semiosis back to the vital background of human experience.

Normal: A Chaplain, a Community with HIV/AIDS, and the Eternal Life of Stories - Kerr, Audrey Elisa (Cascade Books, 2018)
This book chronicles the intersection of chaplaincy, autopathography (illness narratives), and stigmatized illness through the observations and stories of a chaplain working at a facility for people with HIV and AIDS. Trained as both an ethnographer and a chaplain, Audrey Elisa Kerr uses memoir to bridge the relationship between caregiver and patient, and allows stories of marginality to frame both her patients’ stories and her own.
Keywords: dept.eng

Dead Narratives: Defining Humanity through Stories - Ellis, Scott (The Apocalypse in Film: Dystopias, Disasters, and Other Visions about the End of the World, 2015)
We live in a world at risk. Dire predictions about our future or the demise of planet earth persist. Even fictional representations depict narratives of decay and the end of a commonly shared social reality. Along with recurring Hollywood blockbusters that imagine the end of the world, there has been a new wave of zombie features as well as independent films that offer various visions of the future. The Apocalypse in Film: Dystopias, Disasters, and Other Visions about the End of the World offers an overview of Armageddon in film from the silent era to the present. This collection of essays discusses how such films reflect social anxieties—ones that are linked to economic, ecological, and cultural factors. Featuring a broad spectrum of international scholars specializing in different historical genres and methodologies, these essays look at a number of films, including the silent classic The Four Horsemen of the Apocalypse, the black comedy Dr. Strangelove or: How I Learned to Stop Worrying and Love the Bomb, the Mayan calendar disaster epic, 2012, and in particular, Lars Von Trier’s Melancholia, the focus of several essays.As some filmmakers translate the anxiety about a changing global climate and geo-political relations into visions of the apocalypse, others articulate worries about the planet’s future by depicting chemical warfare, environmental disasters, or human made destruction. This book analyzes the emergence of apocalyptic and dystopic narratives and explores the political and social situations on which these films are based. Contributing to the dialogue on dystopic culture in war and peace, The Apocalypse in Film will be of interest to scholars in film and media studies, border studies, gender studies, sociology, and political science.

When I'm done helping with your battles, I've got work to do: Black feminism, white power, and the messy swelling of the margins - Kerr, Audrey E. (Our Voices Our Stories: An Anthology of Writings Advancing, Celebrating, Embracing and Empowering Girls and Women of Color, 2019)
"Our Voices Our Stories" is filled with thought-provoking poems, essays, short stories and other writings advancing, celebrating, embracing and empowering girls, teens and women of color worldwide. The diverse national and international voices represented in this anthology focus on the psychological, emotional, physical and social issues, traumas and challenges experienced by girls, teens and women of color. The writing will encourage society to understand what it means to be a girl, teen and woman of color living in a society that does not always listen to hear their voices or their stories.
Keywords: dept.eng

Black Women Speaking From Within - Hope, Kelly (Peter Lang, 2019)
In Black Women Speaking From Within: Essays and Experiences in Higher Education, contributors use intersectional and interdisciplinary lenses to share the ways in which they understand, navigate, resist, and transform student services, learning, teaching, and existing in the academy. This book explores and discusses the following question: How do Black women experience and perceive place and agency in higher education? Black Women Speaking From Within draws upon the influence organizational culture, sense-making, and sisterhood has on praxis and pedagogy and places the Black woman’s stories and experiences at the center of the conversation.
Keywords: dept.eng

Facing the Other: Responsibility, Convictions and the Ethics of Attachment - Larocco, Steve (The Ethos of Theorizing: Peer-reviewed, Edited and Selected Proceedings of the Seventeenth Biennial Conference of International Society for Theoretical Psychology, Tokyo, Japan, August 2017, 2019)
Keywords: dept.eng; peer-reviewed

Sabbatical Leave Report - Hochman, Will (Distribution: fall-spring-15 ; English., 2015)
From the report: "My goal was to develop, reserach and write my next study on J.D. Salinger. With the aid of research and [sic] on Salinger's letters at the Morgan Library and The Firestone Library (Princeton), and several visits to his Cornish home, I was able to finish one manuscript, begin another, and start a Salinger essay designed to attract interest in my manuscript. I am happy to report that I completed my next manuscript, Harvesting Salinger's Rye, because I earned the tremendous good fortune to recieve support from SCSU."
Keywords: dept.eng; faculty_collection; sabbatical_report

Breathing, One Adult. - Troy, Robin (2012)
Completed 200 pages of a book documenting surviving Hodgkins Lymphoma, a family history describing the experiences both of the author and of her mother.
Keywords: dept.eng; faculty_collection; sabbatical_report

Critical Companion to J.D. Salinger: A Literary Reference to His Life and Work - Mueller, Bruce F.; Hochman, Will (Facts on File library of American literature, 2011)
Keywords: Handbooks, manuals, etc; Salinger, J. D. (Jerome David), 1919-2010; dept.eng; faculty_collection

The Number 43: The Life and Legacy of Wild Bill Greco - Greco, Sarah (Coastal 181, 2018)
Keywords: Stock car racing; United States; United States; Stock car drivers; dept.eng

After Hours: Poems - Mottola, Pat (Five Oaks Press, 2018)
Keywords: dept.eng

Sabbatical project: a Norton critical edition of W. D. Howell's novel, The rise of Silas Lapham (1885) - Petrie, Paul R. (2017)
Keywords: dept.eng; faculty_collection; sabbatical_report

Sabbatical Leave Report Spring 2016: In Search of Mercy Ethnicity, Gender and Parochial Education in Washington Height, New York, and the Catechism of Bella Abzug and Audre Lorde - Kerr, Audrey Elisa (2016)
The purpose of this essay was to expand the ways critics think about Harlem and the Heights following the Great Depression by recovering women's creative responses to social and political angst in predominantly Catholic spaces.
Keywords: dept.eng; faculty_collection; sabbatical_report

Under the Red Dress - Mottola, Pat (Five Oaks Press, 2016)
Keywords: American poetry; dept.eng; faculty_collection

The Religion of Empire: Political Theology in Blake's Prophetic Symbolism - Rosso, G. A. (Literature, religion, and postsecular studies, 2016)
The Religion of Empire: Political Theology in Blake's Prophetic Symbolism is the first full-length study devoted to interpreting Blake's three long poems, showing the ways in which the Bible, myth, and politics merge in his prophetic symbolism. In this book, G. A. Rosso examines the themes of empire and religion through the lens of one of Blake's most distinctive and puzzling images, Rahab, a figure that anchors an account of the development of Blake's political theology in the latter half of his career. Through the Rahab figure, Rosso argues, Blake interweaves the histories of religion and empire in a wide-ranging attack on the conceptual bases of British globalism in the long eighteenth century. This approach reveals the vast potential that the question of religion offers to a reconsideration of Blake's attitude to empire. The Religion of Empire also reevaluates Blake's relationship with Milton, whose influence Blake both affirms and contests in a unique appropriation of Milton's prophetic legacy. In this context, Rosso challenges recent views of Blake as complicit with the nationalism and sexism of his time, expanding the religion-empire nexus to include Blake's esoteric understanding of gender. Foregrounding the role of female characters in the longer prophecies, Rosso discloses the variegated and progressive nature of Blake's apocalyptic humanism.
Keywords: Blake, William, 1757-1827; Criticism and interpretation; Blake, William, 1757-1827; History and criticism; Prophecies in literature; Political and social views; Blake, William, 1757-1827. Four Zoas; Blake, William, 1757-1827. Milton; Blake, William, 1757-1827. Jerusalem; Political theology; Epic poetry, English; Religion; Blake, William, 1757-1827; SCSU Faculty Scholar Award; award_winner; dept.eng

American Woman Suffrage Postcards: A Study and Catalog - Florey, Kenneth (McFarland & Company, Inc., Publishers, 2015)
"American women's suffrage activists were fascinated with suffrage themed postcards. They collected them, exchanged them, wrote about them, used them as fundraisers and organized 'postcard day' campaigns. The cards they produced were imaginative and ideological, advancing arguments for the enfranchisement of women and responding to antisuffrage broadsides. Publishers were also interested in suffrage cards, recognizing their profit potential"--
Keywords: Catalogs; Catalogs; Postcards; History; History; Postcards; Pictorial works; Pictorial works; Women; Political aspects; Suffrage; United States; Women; dept.eng; faculty_collection

Perennial - Shipley, Vivian (Negative Capability Press, 2015)
Keywords: dept.eng; faculty_collection

The Poet - Shipley, Vivian (Louisiana Literature Pres, 2015)
Keywords: dept.eng; faculty_collection

Sabbatical leave report: academic year 2014-15 - Hochman, Will (2014)
Hochman met his goal to develop, research and write a new study on J.D. Salinger. The manuscript "Harvesting Salinger's Rye" was completed and has been submitted to various publishers. He also engaged in non-Salinger scholarship delivering conference papers on creative writing. Hochman also used the sabbatical time to make improvements in his teaching and course content and to engage in professional reading.
Keywords: dept.eng; faculty_collection; sabbatical_report

Fall 2014 Sabbatical Leave Report - Johnson, Brian (2014)
Leave employed to complete draft of full manuscript of new poetry collection, now entitled About to Say.
Keywords: dept.eng; faculty_collection; sabbatical_report

Blinding Light - Beck, Christine (Grayson Books, 2013)
Keywords: dept.eng; faculty_collection

Women's Suffrage Memorabilia: An Illustrated Historical Study - Florey, Kenneth (McFarland & Company, Inc., 2013)
"This work analyzes 70 different categories of suffrage memorabilia, while providing numerous images of relevant objects along the way, and discusses these innovative production methods. Most important, this study looks at period accounts, often fascinating, of how, why, when, and where the memorabilia were used in both America and England"--
Keywords: Collectibles; Women; Great Britain; Suffrage; United States; Women; Women; dept.eng; faculty_collection

Carrying My Father's Torch: A Memoir - Ogbaa, Kalu (Carolina Academic Press, 2013)
Keywords: 1960-; Biography; College teachers; Biography; Fathers and sons; Biography; Igbo (African people); Biography; Immigrants; Biography; Nigeria; Civil War, 1967-1970; Connecticut; Family; Nigerian Americans; History; New Haven; Nigeria; Christian biography; Nigeria; Nigeria; Ogbaa, Kalu; Ogbaa, Kalu; United States; dept.eng; faculty_collection

Fear and What Follows: The Violent Education of a Christian Racist, a Memoir - Parrish, Tim (Willie Morris books in memoir and biography, 2013)
An account of the author's spiral into racist violence during the latter years of desegregation in the 1960s and 1970s Baton Rouge.
Keywords: Baton Rouge; Baton Rouge (La.); Baton Rouge; Racism; Biography; Homes and haunts; Louisiana; Parrish, Tim; Authors, American; Race relations; dept.eng; faculty_collection

The Jumper - Parrish, Tim (Texas Review Press, 2013)
"Set amidst North Baton Rouge's inferno of industries and refineries, smack in the middle of low-rent crime and violence, The jumper is a fast-paced and gritty tale about characters who'd intimidate the thugs of a 1930s hard-boiled novel. Parrish's visceral yet lyrical prose, his structuring of fictional time, and his clear moral vision transform these tough-guy elements into an experience somehow luminescent, emotionally disturbing, and completely uplifting."--Back cover.
Keywords: Fiction; Young men; dept.eng; faculty_collection

Civil Twilight: Poems - Schilpp, Margot (Carnegie Mellon University Press, 2012)
Mad River Literary Festival Collection
Keywords: 21st century; American poetry; dept.eng; faculty_collection

The Networks of New Haven Culture, 1800-1850. - Ellis, Scott (2011)
Sabbatical research investigating the literary culture of New Haven, Connecticut, during the first half of the 19th century, encompasing book importers, booksellers, publishers, newspapers, periodicals, libraries, and literary societies. Based on extensive local collections dispersed throughout local repositories.
Keywords: dept.eng; faculty_collection; sabbatical_report

Liberty Lanes - Troy, Robin (West word fiction series, 2011)
Nelson Moore, one of the bowlers at Liberty Lanes, has recently become a hero by saving a teammate from choking on a chicken bone. Now he must deal with his sudden fame while coping with the early stages of dementia.--(Source of description unspecified.)
Keywords: Age groups; Aged; Aging people; Alleys, Bowling; Aphrenia; Aphronesia; Athletes; Athymia; Bowlers Fiction.; Bowlers.; Bowling alleys Montana.; Bowling lanes; Brain Diseases; Dementia.; Dementias; Država Montana; Elderly people; Electronic books.; Fiction.; Gerontocracy; Gerontology; Lanes, Bowling; MT; Monekana; Montana Eyaleti; Montana Fiction.; Montana Territory; Montana-sh; Montana.; Montanash; Montano; Neurobehavioral disorders; Old age; Old people; Older adults; Older people Fiction.; Older people.; Older persons; Persons; Politeia tēs Montana; Psychoses; Senior citizens; Seniors (Older people); Shtat Montana; Sports facilities; State of Montana; Statul Montana; Stories; Tales; dept.eng; faculty_collection; nne Aged

An Imperative Duty - Howells, William Dean (Broadview editions, 2010)
Keywords: Fiction; Fiction; Passing (Identity); Fiction; Young women; Racially mixed people; dept.eng; faculty_collection

Ruthless: Poems - Mock, Jeff (Three Candles Press, 2010)
Keywords: dept.eng; faculty_collection

Blood and Bravery: Voices of Biafran Veterans of the Nigeria-Biafra War - Ogbaa, Kalu (Sungai, 2010)
Keywords: Civil War, 1967-1970; History; Nigeria; dept.eng; faculty_collection

All of Your Messages Have Been Erased - Shipley, Vivian (Louisiana Literature Press, 2010)
Keywords: dept.eng; faculty_collection

Freud as new woman writer: Maternal ambivalence in Studies on Hysteria - Fluhr, N. (English Literature in Transition, 1880-1920, 2010)
Keywords: dept.eng; ⛔ No DOI found

Woolf’s editorial self-censorship and risk-taking in Jacob’s room - Neverow, V. (Virginia Woolf and the Literary Marketplace, 2010)
Keywords: dept.eng

Virginia Woolf and city Aesthetics - Neverow, V.S. (The Edinburgh Companion to Virginia Woolf and the Arts, 2010)
Keywords: dept.eng

Latin Alive: The survival of Latin in English and the Romance languages - Solodow, J.B. (Latin Alive: The Survival of Latin in English and the Romance Languages, 2010)
In Latin Alive, Joseph Solodow tells the story of how Latin developed into modern French, Spanish, and Italian, and deeply affected English as well. Offering a gripping narrative of language change, Solodow charts Latin's course from classical times to the modern era, with focus on the first millennium of the Common Era. Though the Romance languages evolved directly from Latin, Solodow shows how every important feature of Latin's evolution is also reflected in English. His story includes scores of intriguing etymologies, along with many concrete examples of texts, studies, scholars, anecdotes, and historical events; observations on language; and more. Written with crystalline clarity, this is the first book to tell the story of the Romance languages for the general reader and to illustrate so amply Latin's many-sided survival in English as well. © Joseph B. Solodow 2010.
Keywords: History; History; Latin language; Influence on English; Romance languages; Influence on Romance; Latin language; Latin language; dept.eng; faculty_collection

"Telling what's o'er": Remaking the sonnet cycle in Augusta Webster's Mother and Daughter - Fluhr, N. (Victorian Poetry, 2011)
Keywords: dept.eng

Endless virtue and trinitarian prayer in lancelot’s healing of urry - Holbrook, S.E. (Malory and Christianity: Essays on Sir Thomas Malory's Morte Darthur, 2013)
Keywords: dept.eng

To the well: Malory's Sir Palomides on ideals of chivalric reputation, male friendship, romantic love, religious conversion-and loyalty - Holbrook, S.E. (Arthuriana, 2013)
Although Palomides in Malory's Morte Darthur and his counterpart in the French Tristan en Prose are usually discussed by their roles, my study selects five scenes linked by woodland settings, wells, and complaints. Accordingly, it demonstrates what each scene shows about the values of reputation, friendship, love, religious conviction, and-in the aftermath of the rupture between Lancelot and Arthur-the capacity for loyalty to Lancelot shown by Palomides and his brother Saphir. © 2013 Project MUSE.
Keywords: dept.eng

Representing the modern animal in culture - Dubino, J.; Rashidian, Z.; Smyth, A. (Representing the Modern Animal in Culture, 2014)
Examining a wide range of works, from Gulliver's Travels to The Hunger Games, Representing the Modern Animal in Culture employs key theoretical apparatuses of Animal Studies to literary texts. Contributors address the multifarious modes of animal representation and the range of human-animal interactions that have emerged in the past 300 years. © Jeanne Dubino, Ziba Rashidian, and Andrew Smyth 2014. All rights reserved.
Keywords: Animals in literature; Human-animal relationships in literature; Animals and civilization; dept.eng; faculty_collection

Splicing genes with postmodern teens: The hunger games and the hybrid imagination - Smyth, A. (Representing the Modern Animal, 2014)
Keywords: dept.eng

Hawthorne's Two Bodies: Politics and Aesthetics in Our Old Home - Baraw, C. (Literary Imagination, 2016)
Keywords: dept.eng

Challenging evaluation: The complexity of grading writing in hybrid MOOCs - McEachern, R.W. (Handb. of Res. on Writ. and Compos. in the Age of MOOCs, 2017)
When MOOCs exploded into the public consciousness in 2012, many supporters touted their potential to disrupt higher education. In a short time, MOOCs have evolved, and that role as radical change agents seems to have faded. However, the use of Hybrid MOOCs, in which onground courses use MOOCs for some or all of their content, does have the potential to be disruptive, albeit on a smaller scale. This article will describe one Hybrid MOOC and the ways it could be used to disrupt individual pedagogy, and perhaps affect larger change as a result. © 2017 by IGI Global. All rights reserved.
Keywords: dept.eng

Swinburne: Criticism as perversion - Fluhr, N. (Nineteenth Century Prose, 2016)
Keywords: dept.eng; ⛔ No DOI found

Negotiating pedagogical authority: the rhetoric of writing center tutoring styles and methods - Corbett, Steven J (Rhetoric Review, 2013)
Writing centers have long been rich sites of critical inquiry into individualized instructional styles and methods. One of the great writing center debates involves directive versus nondirective tutoring styles and methods. While many writing center scholars have discussed the intricacies of directive or interventionist versus nondirective or minimalist pedagogical methods, few have examined the rhetorical implications of this important debate in relation to more classroom-based peer collaborations. This article rhetorically analyzes the literature on directive/nondirective methods and various approaches to tutoring writing, drawing pedagogical and rhetorical connections and implications useful for all teachers of writing and rhetoric. © 2013 Copyright Taylor & Francis Group, LLC.
Keywords: dept.eng

‘The Author Makes the Reader Acquainted with His Abode’: Hawthorne as Transatlantic Tour Guide in The Marble Faun and ‘The Old Manse’ - Baraw, Charles (Transatlantic Literature and Author Love in the Nineteenth Century, 2016)
Here the volume continues its reflections on Hawthorne’s career but turns to his place in the literature of ‘homes and haunts’, taking up the question of how literary geography and its localization of authors helped construct an authorial presence for Americans and a tangible transatlantic literary canon. (It turns out that having a home on the literary itinerary was crucial to nineteenth-century reception.) Baraw demonstrates that the poetics of literary tourism provided Hawthorne with both a means of self-canonization as a tourist attraction and a tool for cultivating the ideal ‘English’ reader for his books. This essay begins a strand of chapters related to literary tourism and the construction of international heritage landscapes.
Keywords: American Author; Authorial Persona; Direct Address; Tour Guide; Tourist Attraction; dept.eng

Pain as semiosomatic force: The disarticulation and rearticulation of subjectivity - Larocco, Steve (Subjectivity, 2016)
Scarry's (The Body in Pain: The Making and Unmaking of the World, Oxford, New York, 1985) broke crucial ground in examining the antagonisms between pain, embodiment and language, and the isolating effects of pain as experience. This paper submits Scarry's claim that extreme pain destroys language, evades mediation, and isolates the subject to critical scrutiny, arguing instead that pain is a semiosomatic force, a form of feeling generated by imperative information about embodiment (real or imaginary) that works to disarticulate and move the subject and the social environment. Pain is not predominantly antagonistic to language; rather, pain insists on signifying, with language being only one of its performative media. What pain resists is representation, not the informational force exerted through language and other semiotic forms. Rather than unmaking language, pain disarticulates and rearticulates subjectivity, refashioning interrelations between the body, subjectivity, others, and culture in ongoing processes of largely aversive impingement, embroiling subjectivity with the imperative directives of embodied vulnerability. © 2016 Macmillan Publishers Ltd.
Keywords: dept.eng; embodiment; pain; performativity; semiotics; subjectivity

Invisible debility: attitudes toward the underrepresented in library workplaces - Brown, Mary E (Public Library Quarterly, 2015)
The American Library Association is committed to recruiting persons of color and those with disabilities to the profession, yet these groups are underrepresented among librarians. While intentional discrimination was the impetus for the Civil Rights Act of 1964, empirical studies in the workplace have exposed continued discrimination through unconscious bias. Extending such research to the library profession raises the question: How do librarians perceive the underrepresented as potential fellow library staff? In my recently conducted study of public library staff and future librarians, participants agreed that library staff should represent the diversity of the communities served; there was little support, however, for actively attempting to advance proportional representation through education or hiring. © , Published with license by Taylor & Francis.
Keywords: dept.eng; employment discrimination; hiring bias; peer-reviewed; underrepresentation of minorities in library employment

Is Personality a System? Stability, Process and Plasticity. - Larocco, Steven (Integrative psychological & behavioral science, 2015)
The nomothetic thrust of personality research has been the subject of some significant recent criticism. One major problem is the failure in much personality research to sufficiently scrutinize its methods and its background beliefs. This produces conceptual schematizations of personality that do not sufficiently take into account the disunity and plasticity that affects what is construed as personality; it also underplays the necessity of more fully theorizing the network of infrapsychic and transpersonal systems, processes, structures, templates, interfaces, flows of stimuli, qualities of embodiment and contingencies that dynamically manifest as personality. It is through unfolding the complexity inherent in this network that personality theorization can move forward in new ways. This paper provides a provisional, beginning taxonomy of this network in order to start a research dialogue about personality that doesn't begin with the operative background beliefs of nomothetic methodology, that doesn't tacitly or overtly construe the individual to be a self-regulating, homeostatic system, and that resists presupposing personality as a cohesive, stable quality of personhood.
Keywords: *Personality; *Psychological Theory; Contingency; Embodiment; Five-factor model; Humans; Personality; Personality/cl [Classification]; Plasticity; Plasticizer; Psychological Theory; Stabilizer; classification; dept.eng; human; personality; psychological theory

Ideology, affect, semiotics: towards a non-personal theory of personality. - Larocco, Steve (Integrative psychological & behavioral science, 2014)
Personality theories, as Giordano (2014) argues, often treat Western versions of the self as having universal import. Eastern notions of self, however, offer a dramatically different basis for thinking about what personality might be. This paper, nonetheless, seeks to offer a general framework for theorizing about the epiphenomenon of personality in any culture, asserting that it is an effect of specific histories of ideological practices, semiotic networks and systems, and affect, which engage each other in dialogic and dialectical ways. The interactions of these factors, guided by ideology, regularize behavior and affective dynamics, largely in non-personal ways. Subjects are produced and reproduced from these complex interactions, which are situationally specific and simultaneously transpersonal. The subjects formed through these interactions are the basis for the folk psychology of personality, which treats the transient, varying effects of these interactions as more or less reified qualities that form a basis for the construction of selfhood, however conceived.
Keywords: *Affect; *Culture; *Personality; *Psychological Theory; Affect; Culture; Five-Factor Model; Humans; Ideology; Personality; Psychological Theory; Semiotics; affect; cultural anthropology; dept.eng; human; personality; psychological theory

Experiencing a social network in an organizational context the facebook internship - Mceachern, Robert W (Business Communication Quarterly, 2011)
As Facebook becomes increasingly more popular as a communication tool for businesses and organizations, it is important that our students learn to transfer personal Facebook skills to professional settings. This article focuses on the lessons learned by two students who used Facebook as part of a social media internship, as well as what the author learned about its use through research and teaching a course on social media and professional writing. © 2011 Association for Business Communication.
Keywords: Facebook; dept.eng; internships; social media

Guenevere: the abbess of amesbury and the mark of reparation - Holbrook, Sue Ellen (Arthuriana, 2010)
Malory elevates Guenevere to abbess ofAmesbury where she heals her soul through a penitential process clarified by Cassian's teachings on attitude and supplication and by the cloister context and devotional formulas of her speech on salvation. (SEH).
Keywords: dept.eng

Milton - Rosso, G. A. (William Blake in Context, 2019)
Keywords: dept.eng; faculty_collection

Brown and the Yellow Fever - Ellis, Scott (The Oxford Handbook of Charles Brockden Brown, 2019)
The Oxford Handbook of Charles Brockden Brown provides an up-to-date survey of the life of and full range of writings by Charles Brockden Brown (1771–1810), a key writer of the Atlantic revolutionary age and U.S. Early Republic. Through the late twentieth century, Brockden Brown was best known as an important author of political romances in the gothic mode that were widely influential in romantic era, and has generated large amounts of scholarship as a crucial figure in the history of the American novel. More recent work recognizes him likewise an influential editor, historian, and writer in other genres such as poetry, short fiction, and essays, and as a figure whose work resonated throughout the Atlantic world of the revolutionary age. The Oxford Handbook’s thirty-five chapters build on the research of the most recently scholarly generation to introduce readers to and explore Brown’s wide-ranging work. Its chapters focus on the author’s biography, romances, writings in a range of genres, his key concept of the romance as a form of engaged conjectural history, his engagements in the cultural-ideological struggles of the revolutionary and Napoleonic eras, as well as the aesthetic, political, scientific, and other key dimensions of his corpus. The volume concludes with a survey of Brown’s complex reception history and the state of Brown studies at present.
Keywords: dept.eng; faculty_collection

An Archaeology of Days - Shipley, Vivian (Negative Capability Press, 2019)
An Archaelogy of Days contains new poetry from Vivian Shipley. Connecticut State University Distinguished Professor, Vivian Shipley teachesat Southern Connecticut State University where she was named FacultyScholar in 2000, 2005 and 2008. Her eleventh book, Perennial, was publishedin 2015 by Negative Capability Press and was nominated for the PulitzerPrize and named the Paterson Poetry Prize Finalist. The Poet, her tenth book,was published in 2015 by Louisiana Literature Press, Southeastern LouisianaUniversity. All of Your Messages Have Been Erased (Louisiana Literature Press,SLU, 2010) was nominated for the Pulitzer Prize, won the Sheila MottonBook Prize from the New England Poetry Club, the Paterson Award forSustained Literary Achievement and the CT Press Club Award for BestCreative Writing. Her sixth chapbook is Greatest Hits: 1974-2010 (PuddingHouse Press, Youngstown, Ohio, 2010). She has received the Library ofCongress’s Connecticut Lifetime Achievement Award for Service to theLiterary Community and a Connecticut Book Award for Poetry two times.Most recently, she won the 2017-18 Steve Kowit Prize for Poetry for “Cargo”from San Diego Arts & Entertainment Guild. In 2015, she won the HackneyLiterary Award for Poetry for “Foxfire.”
Keywords: 21st century; American poetry; dept.eng; faculty_collection

Pinkwashing - Blackmer, Corinne E. (Israel Studies, 2019)
Keywords: dept.eng; peer-reviewed

Louise Rosenblatt: The reader, democracy, and the ethics of reading - Sinclair, Meredith N. (Reading as Democracy in Crisis: Interpretation, Theory, History, 2019)
Reading as Democracy in Crisis: Interpretation, Theory, History explores the dialectic between historical conditions and the reading strategies that arise from them. It explores the relationship...
Keywords: dept.eng

The Other, Shame, and Politics: Levinas, Justice, and Feeling Responsible - Larocco, Steve (Religions, 2018)
Adi Ophir has suggested that the political realm is an order of evils, producing and managing regular forms of suffering and violence rather than eliminating them. Thus, the political is always to some extent a corrupted order of justice. Emmanuel Levinas’ work presents in its focus on the face-to-face relationship a means of rethinking how to make the political more open to compassionate justice. Though Levinas himself doesn’t sufficiently take on this question, I argue that his work facilitates a way of thinking about commiserative shame that provides a means to connect the face-to-face to its potential effects in the political sphere. If such shame isn’t ignored or bypassed, it produces an unsettling relation to the other that in its adversity motivates a kind of responsibility and care for the other that can alter the public sphere.
Keywords: Commiseration; Evil; Guilt; Law; Levinas; Other; Politics; Responsibility; Shame; Sympathy; commiseration; dept.eng; evil; guilt; law; other; peer-reviewed; politics; responsibility; shame; sympathy

Teaching race, gender, and narrative form in Gertrude Stein’s “Melanctha.’ - Blackmer, Corinne E. (Approaches to Teaching the Works of Gertrude Stein, 2018)
A trailblazing modernist, Gertrude Stein studied psychology at Radcliffe with William James and went on to train as a medical doctor before coming out as a lesbian and moving to Paris, where she collected contemporary art and wrote poetry, novels, and libretti. Known as a writers writer, she has influenced every generation of American writers since her death in 1946 and remains avant-garde.Part 1 of this volume, Materials, provides information and resources that will help teachers and students begin and pursue their study of Stein. The essays of part 2, Approaches, introduce major topics to be covered in the classroomrace, gender, feminism, sexuality, narrative form, identity, and Steins experimentation with genrein a wide range of contexts, including literary analysis, art history, first-year composition, and cultural studies.
Keywords: dept.eng

The divine sublime: Educating spiritual teachers in Emerson’s divinity school address - Blackmer, Corinne E. (Approaches to Teaching the Works of Ralph Waldo Emerson, 2018)
A leader of the transcendentalist movement and one of the country's first public intellectuals, Ralph Waldo Emerson has been a long-standing presence in American literature courses. Today he is remembered for his essays, but in the nineteenth century he was also known as a poet and orator who engaged with issues such as religion, nature, education, and abolition.This volume presents strategies for placing Emerson in the context of his time, for illuminating his rhetorical techniques, and for tracing his influence into the present day and around the world. Part 1, "Materials," offers guidance for selecting classroom editions and information on Emerson's life, contexts, and reception. Part 2, "Approaches," provides suggestions for teaching Emerson's works in a variety of courses, not only literature but also creative writing, religion, digital humanities, media studies, and environmental studies. The essays in this section address Emerson's most frequently anthologized works, such as Nature and "Self-Reliance," along with other texts including sermons, lectures, journals, and poems.
Keywords: Language Arts & Disciplines / Study & Teaching; Literary Criticism / American / General; Literary Criticism / Modern / 19th Century; dept.eng

Reading curriculum in the age of spectacle: Reclaiming experience and dialogue in reading - Sinclair, Meredith N. (Journal of Curriculum Theorizing, 2018)
Using Fahrenheit 451 as a model for reading in the age of spectacle, this paper offers a critique of reading curriculum driven by Common Core State Standards for English Language Arts and Literacy in History/Social Studies, Science, and Technical Subjects (CCSS-ELA), which divorces reading from dialogue and lived experience.  Drawing on Debord’s (1967/1983) notion of spectacle, the author considers how our current cultural moment may be shaping and shaped by an alienated and alienating curriculum of reading.  By embracing the political implications of reading curriculum, we can reclaim reading as a dialogic activity grounded in the world.
Keywords: dept.eng; literacy; peer-reviewed; reading; ⛔ No DOI found

Fluid boundaries in 'The Awntyrs off Arthure' and 'Sir Isumbras' - Richmond, Andrew (Open Library of Humanities, 2018)
Encounters with water shape the Middle English romances of The Awntyrs off Arthure and Sir Isumbras. In the latter, rivers and the 'Greek Sea' serve to distinguish separate sections of the narrative: the river marks the point at which the titular hero's family unit begins to break down, while the beach of the sea marks the lowest point of his social power. Yet his later traversal of the Greek Sea itself allows him to reassemble his family and reclaim his aristocratic power. In Awntyrs, the Tarn Wathelene (or Wadling) ties the actions of the romance's first episode onto a specific spot in the real-world English landscape, while connecting the text to a number of other Arthurian romances that also mention or take place near the tarn. This article, then, argues that the waterscapes in these two texts illustrate a late-medieval understanding of tarns, rivers, and seas as explicitly alien, yet intimately physical embodiments of divine power in the natural world. Taken together, these poems-one a metrical romance, the other alliterative-show how interests in waterscapes crossed boundaries within the muddy genre of romance itself, and reveal that water upsets such human categories as family and property. Tarns, rivers, and seas turn human bodies, instead, into their possessions; the disturbing experience of that dehumanizing process should, these texts imply, wear the world, its history, and its bonds away, until even the greatest knights or ladies are left alone with watery forms beyond the pale of human understanding. © 2018 The Author(s).
Keywords: dept.eng; peer-reviewed

The Rise of Silas Lapham: Authoritative Text, Contexts, Criticism - Howells, William Dean (Norton critical edition, 2018)
Keywords: Fiction; Fiction; Domestic fiction; Psychological fiction; Boston (Mass.); Fiction; Rich people; Fiction; Socialites; Howells, William Dean, 1837-1920. Rise of Silas Lapham; Businessmen; dept.eng

Science and technology in Hawthorne’s short fiction - Ellis, Scott (Nathaniel Hawthorne in the College Classroom: Contexts, Materials, and Approaches, 2018)
This new work is currently the only book devoted to the teaching of one of the most canonical and frequently taught American authors.In addition to a Preface by the noted Hawthorne scholar Larry J. Reynolds [University Distinguished Professor and Thomas Franklin Mayo Professor of Liberal Arts Department of English Texas A&M University] the contributors include well-known and rising teacher-scholars who offer theoretical and pedagogical approaches to Hawthorne's four published novels and a wide range of his short stories.The specially commissioned essays are designed to help teachers meet students at points of genuine interest and need. They incorporate biographical, literary, historical, and multidisciplinary scholarship. The studies are further grounded in specific contexts such as literature surveys, interdisciplinary humanities courses, upper division literature seminars, and study abroad courses.Special emphasis is given to the issues of gender, science, and visual culture (including film adaptations). Offering both theoretical and practical classroom resources, this anthology confirms the continued vitality of Hawthorne's work - his critiques of religious and moral authority are more relevant than ever in today's global political environment - even as it showcases how today's "Hawthorne" is more of a diverse amalgam of texts and perspectives than ever before. Given its diversity of approaches and authors (including essayists from Germany, Israel, and Sweden), Nathaniel Hawthorne in the College Classroom charts new paths for reading and teaching Hawthorne in the 21st century.
Keywords: dept.eng

Reaping something new: African American transformations of Victorian literature. - Baraw, Charles (Journal of British Studies, 2018)
Keywords: dept.eng; peer-reviewed

States of the Union - Papa, Michaela (Mascot Books, 2018)
In nonfiction, poetry, short fiction, artwork, and detailed interviews, States of the Union collects reflections from everyday Americans on the 2016 presidential election. -Publisher Web Site.
Keywords: 2016; Election; Presidents; United States; dept.eng; faculty_collection

Can we be part of the pride? Reading animals through comics in the undergraduate classroom - Baraw, Charles; Smyth, Andrew (Animal comics: Multispecies storyworlds in graphic narratives, 2017)
Animal characters abound in graphic narratives ranging from Krazy Kat and Maus to WE3 and Terra Formars. Exploring these and other multispecies storyworlds presented in words and images, Animal Comics draws together work in comics studies, narrative theory, and cross-disciplinary research on animal environments and human-animal relationships to shed new light on comics and graphic novels in which animal agents play a significant role. At the same time, the volume's international team of contributors show how the distinctive structures and affordances of graphic narratives foreground key questions about trans-species entanglements in a more-than-human world. The writers/artists covered in the book include: Nick Abadzis, Adolpho Avril, Jeffrey Brown, Sue Coe, Matt Dembicki, Olivier Deprez, J. J. Grandville, George Herriman, Adam Hines, William Hogarth, Grant Morrison, Osamu Tezuka, Frank Quitely, Yu Sasuga, Charles M. Schultz, Art Spiegelman, Fiona Staples, Ken'ichi Tachibana, Brian K. Vaughan, and others.
Keywords: Art / Subjects & Themes / Landscapes & Seascapes; Comics & Graphic Novels / Literary; Humor / Form / Comic Strips & Cartoons; Literary Criticism / Comics & Graphic Novels; dept.eng

Spleen elegy - Labbe, Jason (BlazeVOX [books], 2017)
Let’s twin and twine together two primary aspects of how America can see herself—the good atoms of Whitman’s leaves of grass, and the engines humming their freedom on the highways that cut across those 19th century fields. Now, Jason Labbe well knows, as Whitman’s atoms become pixels, we find ourselves at a crossroads, learning again and again the consequences of “the indescribable way you shape / a past of little use.” Seeking to find that law or logic to shattering, be it in the memory-echo of personal trauma caught on infinite loop in the mind, or be it the dismal virtualities of the post-modern ether, the poems of Spleen Elegy unfold their rueful nostalgia: “I have something accurate to say that lacks perspective.” That may well be the very accuracy we most need, riding the routes of America, the byways and frontage roads, seeking anyone who is willing for a poem or two to see. —Dan Beachy-Quick "A chunk of broken tar”—that's the color of this book. And the sound of this book is "a train in the static." Its poems count time in "decaseconds of dusk." To read this book is to feel the uneasy passivity and unerring stuckness, the particular absurdity, of certain citizens stuck in this millennium. So many lines made me laugh. And sigh. But not cry. Jason Labbe is great at melancholy. Baudelaire's mosquito is definitely here: "I am Past / who passing lit and sucked your life and left." The future is unthinkable and unalterable. Except. Except! Lucretius' swerve is also here. Atoms may veer randomly, which is extra significant in a book that takes place mostly on the road. "My sutures are beautiful as a tread pattern," he says, and it is easy (and dangerous) to fall in love with Labbe's strangled version of optimism. —Darcie Dennigan
Keywords: dept.eng

Foucault, confession, and Donne - Dodson, Joel M. (Forms of faith, 2017)
Keywords: dept.eng

Empathy as Orientation Rather than Feeling: Why Empathy Is Ethically Complex - Larocco, Steve (Exploring Empathy, 2017)
"Empathy as Orientation Rather than Feeling: Why Empathy Is Ethically Complex" published on 01 Jan 2017 by Brill | Rodopi.
Keywords: dept.eng

Hawthorne, a pilgrimage to Salem, and the poetics of literary tourism - Baraw, Charles (Canadian Review of American Studies, 2017)
From the 1830s to the end of his career, Nathaniel Hawthorne used the tropes of aesthetic tourism to call out, or interpellate, the reader as a literary tourist. In many cases, Hawthorne’s focalizi...
Keywords: "Alice Doane's appeal" Caroline Gilman; Literary tourism; Narrative poetics; Nathaniel Hawthorne; Samuel Gilman; Touristic poetics; dept.eng